Industrial metaverse – company perspectives - Salminen, Karoliina; Aromaa, Susanna (Procedia computer science, 2024)
The utilisation of the industrial metaverse is a topical discussion in the research community as well as within industrial companies. This study aimed to identify industry expectations towards the industrial metaverse. A questionnaire was sent to 18 companies to collect their views on potential industrial metaverse use cases and possible challenges that may occur. The companies identified use cases under eight thematic groups: remote operation and maintenance, sales and marketing, training, guidance and support, knowledge sharing and collaboration, novel services and business opportunities, and flexible utilization and workforce availability. Companies pointed out that challenges in using the metaverse may originate from technology acceptance, technology maturity, data governance, regulations and standards, cyber security and safety and cost. These findings provide company perspective on the industrial metaverse discussion and can be used when researching the topic and developing metaverse solutions further.